THE IMPACT OF CONCEPT CARTOONS AS AN INSTRUCTIONAL MATERIAL AND FORMATIVE ASSESSMENT TOOL IN TEACHING EVOLUTION ON THE ACHIEVEMENT OF GRADE 11 STEM STUDENTS ENROLLED IN SYNCHRONOUS MODALITY - Hizon, Jade O; Cruz, Nikki Y; Collantes, Leila M.; Torres, Joel M.; Mukminin, Amirul; Ibarra, Florante P. (LPPM Universitas Jambi, 2024)
Employing a pretest-posttest quasi-experimental design, this study ventures into uncharted territory by investigating the impact of Concept Cartoons as a pedagogical tool in teaching Evolution on the academic performance of 40 Grade 11 STEM students enrolled in General Biology 2, conducted synchronously. Furthermore, the research pioneers an exploration into students' misconceptions surrounding foundational concepts in Evolution, leveraging Concept Cartoons as a formative assessment tool deployed within an online learning platform. The cohort was divided into control (n = 21) and experimental (n = 19) groups, with the former receiving instruction through traditional lecture methods and the latter through Concept Cartoons administered digitally. Surprisingly, while students exhibited a spectrum of misconceptions related to Evolution, both experimental and control groups demonstrated statistically significant improvements in academic achievement from pre-test to post-test. Intriguingly, however, comparison of post-test scores between the experimental and control groups via independent t-test yielded no significant difference in achievement. This incongruity prompted a nuanced discussion on potential contributing factors, including the efficacy of Concept Cartoons in digital media and unforeseen technical challenges encountered during synchronous instruction. These findings offer valuable insights for science educators navigating the transition from face-to-face to online instruction amid the ongoing pandemic, underscoring the importance of critically evaluating the adaptability and effectiveness of instructional materials within diverse learning modalities.